Utilization of a cascoded-inverter in an RGC structure as a low-power, broadband TIA. (May 2020) - Hosseinisharif, Seyed Ali; Pourahmadi, Majid; Shayesteh, Mohammad Reza
Abstract: A low-power circuit structure is reported in this paper as a broadband TIA, in which the DC current and hence the power dissipation is lessened by applying cascoded structure to an inverter as an active-feedback network to a conventional Regulated Cascode (RGC) circuit. The improved RGC structure also benefits from an added active-inductor at the output node, which resonates with the output capacitance and provides extra bandwidth without the requirement of excessive current. Results for the proposed RGC-based TIA, which operates at 10 ​Gb/s, show only 1.6 ​mW power dissipation for obtaining 40 ​dBΩ transimpedance gain, 6.4 ​GHz frequency bandwidth and 25pA/√Hz input referred noise. Analysis indicate that the proposed TIA is suitable to work as a transimpedance amplifier in low-power, broadband optical communication receivers.